2020
DOI: 10.3389/fpsyt.2019.00973
|View full text |Cite
|
Sign up to set email alerts
|

Trait-Based Emotional Intelligence, Body Image Dissatisfaction, and HRQoL in Children

Abstract: Background: Body image dissatisfaction (BID) is related to an increased risk for various health issues including descreased health-related quality of life (HRQoL), the development of problematic eating behaviors and obesity. Previous research indicates that emotional intelligence is one important factor related to BID in adults. Whether this is the case in children, remains yet unknown. Taking this into consideration, the aim of this study was to explore the relationship between BID and trait-based emotion int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 57 publications
0
11
0
1
Order By: Relevance
“…The remaining 47 articles were evaluated for inclusion by reviewing their full text and resulted in the exclusion of 38 records for the following reasons: (1) they did not employ cross-sectional/cohort studies ( n = 5), (2) EI was not a predictor ( n = 11) or (3) participants had a mean age of ≥18 years ( n = 22). Finally, 9 articles [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ] were included in the systematic mapping review ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The remaining 47 articles were evaluated for inclusion by reviewing their full text and resulted in the exclusion of 38 records for the following reasons: (1) they did not employ cross-sectional/cohort studies ( n = 5), (2) EI was not a predictor ( n = 11) or (3) participants had a mean age of ≥18 years ( n = 22). Finally, 9 articles [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ] were included in the systematic mapping review ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A description of the included studies is reported in Table 1 . The included articles were published between 2007 [ 35 ] and 2020 [ 34 , 38 ] in China [ 39 , 40 ], Spain [ 34 , 42 ], Germany [ 38 ], France [ 36 ], Mexico [ 41 ], Taiwan [ 37 ] and the United States [ 35 ]. All studies employed a cross-sectional design.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…HRQoL has garnered attention in the literature and in practice to serve as a more specific measure of QoL ( Latas et al, 2014 ). This, too, has a far-reaching application in the literature, ranging from women’s health ( Zhu et al, 2016 ) to adolescent body image ( Pollatos et al, 2020 ) and from stroke research ( Martino Cinnera et al, 2020 ) to epilepsy ( Reilly et al, 2020 ). HRQoL is also among the top measured variables in much of the cancer survivorship literature ( Backemar et al, 2020 ; Bayley-Veloso et al, 2020 ; Grössmann et al, 2020 ; Rammant et al, 2020 ).…”
Section: Measuring Health-related Quality Of Lifementioning
confidence: 99%